AKUNTABILITAS ORGANISASI SEKTOR PUBLIK UNIVERSITAS RIAU (STUDI KASUS PRAKTIK UANG KULIAH TUNGGAL) - Ade Irma Khairani Dita S; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Accountability is a concept that focuses on the capacity of public sector organizations to provide answers to parties with an interest in the organization. Accountability the University of Riau Public Sector Organization (Case Study of Single Tuition Practice) it was found that the problem was the indication of some university students who were not accountable in the group setting for Single Tuition. The purpose of this study is to find out how accountability and inhibiting factors in the practice of Single Tuition. Is the theoretical concept used by the writers is accountability dimention by Litvack and Seddon which consists of: transparency, accountability, participation, and responsiveness. The research method used is a type of qualitative research case study approach, the selection of informants using the snowball sampling technique. The techniques of collecting data are through observation, interviews, library studies, and documentation. The results of this study at the University of Riau as an organization in the public sector in the practice of Single Tuition show an optimal level of accountability. The inhibiting factors include human resources, operational costs, and geographical factors of the region. It’s better if the University of Riau is expected to apply more stringent sanctions to university students who commit fraud, so that university students are bold and for the future, no longer cheating. The student institutions are expected to maintain good relations of coordination with the University of Riau. To university students be able to instill a culture of honesty, give data that is truly real so as not to close the opportunity for other students who need it more.Keywords: Accountability, Public Sector Organizations, Single Tuition